Application and Implementation of BOPPPS Model in Comprehensive Business English --Taking Business English Teaching in Linyi University as an Example - Zhao, Jie (Pacific International Journal, 2024)
In order to better utilize advanced information technology to assist university business English teaching and improve the quality of the teaching, the BOPPPS teaching mode and the online-offline blended teaching mode should be integrated, which is “dual-mode” teaching. This research firstly introduced the BOPPPS model. Based on the theoretical foundation of BOPPPS model, it is combined with practical cases- Unit 7 Enterprise Internationalization of Comprehensive Business English 2 from the six dimensions of lead-in, objectives, pre-test, participatory learning, post-test, and summary with specific examples to elaborate how to apply this model for teaching design and implementation in Comprehensive Business English. Teaching practice shows that the combination of the two teaching modes and the adjustment of the teaching sessions help students to consolidate the foundation of English language knowledge, cultivate the ability of independent learning, group facilitation and pragmatic skills, improve cultural literacy, national pride and self-confidence, and provide a reference for the improvement of the efficiency of the teaching of comprehensive English courses in universities.